Portrait of a killer : Jack the Ripper, case closed - Cornwell, Patricia Daniels (London : Time Warner Books, 2002)
Crime writer Patricia Cornwell uses historical documents and modern technological advances to try and identify the nineteenth-century killer Jack the Ripper.
Includes bibliographical references and index.
Booklist
Pub Weekly
Reference and Research Book News
Adult
Adult
Keywords: Jack, -- the Ripper; Jack, -- the Ripper; Serial murders -- England -- London -- History -- 19th century; Serial murders -- History; Whitechapel (London, England) -- History; Whitechapel (London, England) -- History